1987
DOI: 10.1093/nar/15.20.8399
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of the human α1-antitrypsin gene is controlled by multiple cis-regulatory elements

Abstract: Human alpha 1-antitrypsin (AAT) is expressed in the liver, and a 318 bp fragment immediately flanking the CAP site of the gene was found to be sufficient to drive the expression of a reporter gene (CAT) specifically in hepatoma cells. The enhancing activity however, was orientation-dependent. The DNA fragment was separated into a distal region and a proximal region. A "core enhancer" sequence GTGGTTTC is present within the distal region and is capable of activity enhancement in both orientations when complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…The cis-acting elements required for expression of the human AAT gene in the liver have previously been defined by gene transfer experiments (11,14,66), and nuclear factors that interact specifically with the cis-acting elements have been detected in hepatoma and liver cells (14,66). The crucial questions regarding the nature and mechanism of action of the nuclear factors that must operate through these sequences remain to be answered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cis-acting elements required for expression of the human AAT gene in the liver have previously been defined by gene transfer experiments (11,14,66), and nuclear factors that interact specifically with the cis-acting elements have been detected in hepatoma and liver cells (14,66). The crucial questions regarding the nature and mechanism of action of the nuclear factors that must operate through these sequences remain to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…DNase I footprinting assays (21) were performed as described previously by Shen et al (66). A 20-,ul reaction mixture containing 18 mM HEPES (pH 7.9), 90 mM KCI, 4.5 mM MgCl2, 0.2 mM EDTA, 1.8 mM DDT, 18% glycerol, 1 ,ug of poly(dI-dC), and 1 to 3 ng of 32P-end-labeled HpaII-Hinfl (-150 to +46) fragment was incubated with rat liver or HeLa nuclear extract at room temperature for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In subsequent studies, HNF-1 was purified and found to be 88 kD , and the purified protein was shown to bind to functional sequences within the promoters of albumin at a site that had previously been termed the albumin B box (Lichtsteiner et al 1987) or the albumin proximal region (Cereghini et al 1987). In addition, purified HNF-1 was found to bind to the al-antitrypsin, a fetoprotein, transthyretin, and the pre-S1 promoter of the hepatitis B virus at sites that had been implicated in the tissue-specific expression of these genes Costa et al 1986Costa et al , 1989Godbout et al 1986;Shen et al 1987;Burk et al 1988;Hardon et al 1988;Li et al 1988;Monaci et al 1988). Furthermore, most of the tissue specificity of the albumin promoter could be attributed to a site for the C/EBP protein (Johnson et al 1987;Landschulz et al 1988) and to a region termed the albumin B box or the albumin proximal sequence (Gorski et al 1986;Cereghini et al 1988;Lichtsteiner and Schibler 1989).…”
mentioning
confidence: 99%